National Social Identity in Guinea-Bissau: An Exploratory Essay Inspired by The Methodology of J. Cheek, S. Briggs, S. Smith and L. Tropp - Proença, Carlos Sangreman; Faria, Raquel; Magalhães, José (Advances in Social Sciences Research Journal, 2023)
The research is defined as exploratory and aims to evaluate whether the methodology of inquiry and analysis of the identity of J. Cheek, S.Briggs, S.Smith and L.Tropp [8], can be adapted to a fragile state like Guinea-Bissau. This methodology consists in the assessment of the importance attributed by the respondents of 70 sentences from which the characteristics of individual and social identity (family and collective) are extracted (Cheek, J.M. & Briggs, S.R. [7]). The phrases were sent by digital means to 102 Guineans known in person or only by Facebook with a request for response and dissemination and obtained 183 responses. These answers, calculated according to the methodology adopted, allowed to define some identity characteristics of the respondents. We tried to interpret these results using other surveys conducted since 2014 in Guinea-Bissau with different themes. It is concluded by realizing that this is a method that can contribute to the knowledge of the national identity of Guineans, but insufficient. This conclusion remains to be demonstrated if it is carried out with a statistically significant sample.